2020
DOI: 10.31234/osf.io/z76hg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive and sensory expectations independently shape musical expectancy and pleasure

Abstract: Expectation is crucial for our enjoyment of music, yet the underlying generative mechanism remains contested. While sensory–acoustic models derive predictions based on the short-term auditory input alone, cognitive models assume the use of abstract knowledge of music structure acquired over the long-term. To evaluate these two contrasting mechanisms, we compared simulations from computational models of musical expectancy against subjective surprise ratings of chords sampled from US Billboard pop songs in music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…In addition to veridical and schematic memory for harmony, sensitivity to sensory dissonance could also have had a role in the assessment of the clash chords in our experiment. A recent study asked participants with varying levels of music training to rate harmonic surprise in block-chord instantiations of chord progressions from commercially successful songs (Cheung et al, 2020). The study showed that harmonic surprise could be predicted by a combination of cognitive factors (long-term and short-term statistical learning) and sensory factors (dissonance accumulated in echoic memory).…”
Section: Participant Variablesmentioning
confidence: 99%
“…In addition to veridical and schematic memory for harmony, sensitivity to sensory dissonance could also have had a role in the assessment of the clash chords in our experiment. A recent study asked participants with varying levels of music training to rate harmonic surprise in block-chord instantiations of chord progressions from commercially successful songs (Cheung et al, 2020). The study showed that harmonic surprise could be predicted by a combination of cognitive factors (long-term and short-term statistical learning) and sensory factors (dissonance accumulated in echoic memory).…”
Section: Participant Variablesmentioning
confidence: 99%